Impact of Assam Skill Development Mission among the youth of Guwahati city - Mochahari, Subung; Barman, Juri (The journal of contemporary issues in business and government, 2021)
Unemployment of youth has been a serious problem in the state of Assam over a long period of time. As per the data released by Centre for Monitoring Indian Economy (CMIE), the unemployment rate of Assam in January 2016 was 5.9 and 4.0 in November 2020. In December 2020 the rate started rising and touched the figure of 7.6. The lockdown of economic activities due to Covid-19 Pandemic has worsened the situation. To tackle this issue Assam Government has given priority to skill development and promotion of entrepreneurship in the state. Assam Skill Development Mission has been playing an important role in enhancing skill of youths to increase employability and promote entrepreneurship in Assam since 2017. ASDM is working with many training partners covering all the 33 districts of Assam and also encouraging industries to collaborate with the government for industry integrated training and placement. Although these initiatives are quite appreciative, still the youths of Assam are facing some challenges which cause hindrance in getting their employment. Therefore, it is very important to study the impact and outcome of various training programs under ASDM on youth in getting employment. Moreover the current crisis situation due to COVID-19 has taken way jobs of many and left them unemployed. This study will help to know about different initiatives taken by ASDM in providing employment through skill development and to understand its impact and identify the problems which require serious attention of policy maker for sustainable solution.